Terapi Komplementer terhadap Kebutuhan Dasar Pasien CKD on HD - I Made Sumaharianta Radin; Agung Waluyo; Riri Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of complementary therapy on the basic needs of patients undergoing hemodialysis, especially patients who experience common health problems in patients undergoing hemodialysis, such as anxiety, pain, quality of life, and quality of sleep in patients. The research method used is a systematic review. The results showed that the reduced need for sleep and rest in CKD patients undergoing hemodialysis could be overcome by providing interventions such as listening to music. The need to protect oneself from pain can be recommended by laughter therapy. The need to express emotions and overcome fears can be overcome by providing aromatherapy. In conclusion, the need for CKD patients to move and maintain posture can be met by providing massage therapy to the upper and lower extremities. Keywords: CKD, HD, Complementary Therapy